Passive acoustic monitoring data recorded by recorder AU0085 at mooring AWI251-3 in the Weddell Sea, Southern Ocean, from 2019 to 2021 - Karolin Thomisch; Stefanie Spiesecke; Diego Filun; Marlene Meister; Clea Parcerisas; Irene Roca; Sarah Zwicker; Olaf Boebel (PANGAEA, 2025)
Passive acoustic monitoring (PAM) data were collected by recorder AU0085 of type AURAL (Autonomous Underwater Recorder for Acoustic Listening (AURAL; Model 2, Multi-Électronique) at 61.023° S, 55.978° W, mooring AWI251-3, in the Weddell Sea, Atlantic sector of the Southern Ocean. During a deployment period from February 2019 to April 2022, passive acoustic data were collected from February 2019 to February 2021 by AU0085 as part of the Hybrid Antarctic Float Observing System (HAFOS) in the Weddell Sea. The recorder was moored at 179 m depth and scheduled to record at a duty cycle of 6 min per hour at a sample rate of 32,768 Hz. Further details about the data acquisition and processing of this data set can be found in the accompanying metadata file (see Additional metadata) as well as the data processing report (see Data Processing Report). Passive acoustic data archived here represent data processing Level 1+, according to the standards defined in the associated Standard Operation Procedure (SOP) Glossary (Thomisch et al. 2023a). Further information on data processing with regard to data preparation and standardization can be found in the associated SOP Part 1: Data preparation and standardization (Thomisch et al. 2023b).